Activin A in perinatal brain injury - Brackmann, Florian; Alzheimer, Christian; Trollmann, Regina (Neuropediatrics, 2015)
Activin A is a multifunctional growth and differentiation factor belonging to the transforming growth factor ? (TGF-?) family. Growing evidence indicates its role as a neurotrophic factor and regulator of synaptic transmission as well as its functional importance in several types of cerebral injury. We recently described age-dependent expression of activin A and its regulation at the mRNA and protein level under different conditions of global hypoxia in the neonatal mouse brain. This review discusses the current knowledge of the function and regulation of activin A from human studies as well as from experimental models of brain injury focusing on acquired lesions of the developing rodent brain during the early stages of brain maturation.
EVALuna2:2466